Implementasi Vogel’s Approximation Method (VAM) dan Modified Distribution (Modi) untuk Minimasi Biaya Distribusi di PT Jimat Perkasa Farm - Mukhammad Lucky Bharka Alaik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Efficient and effective distribution management is a key factor in the success of a company's operations. PT Jimat Perkasa Farm, which is engaged in the processing of seaweed waste for animal feed blends, faces significant challenges in minimizing distribution costs. This research aims to implement Vogel's Approximation Method (VAM) and Modified Distribution (MODI) to achieve an optimal solution in reducing distribution costs. The results show that the application of VAM as the initial solution and MODI as the optimal solution is able to produce significant distribution cost savings. The total distribution cost can be minimized from IDR 5,400,000 per month to IDR 5,275,000 per month, which shows a savings of IDR 125,000 / by 2.31% per month. This efficiency in distribution not only reduces operational costs but also improves the timeliness and reliability of delivery, which ultimately improves customer satisfaction and the company's competitiveness in the market